Temporal and regional variabilities in the attenuation of sinking particulate organic carbon in the Kuroshio region - Fukuda, Hideki; Hidaka, Kiyotaka; Setou, Takashi; Kusaka, Akira; Ambe, Daisuke; Saito, Hiroaki (Frontiers in Marine Science, 2022)
The biological pump that transports carbon from the surface ocean to the ocean interior is an important determinant of ocean carbon absorption from the atmosphere, and of biological activity beneath the euphotic zone. Various factors influence the magnitude and efficiency of this biological pump, such as primary production, particle size, and the composition of consumers of particulate organic carbon (POC). The complex factors influencing the biological pump induce high regional and temporal variability; however, the mechanisms of this variability are not understood and its causes remain unclear. The size of sinking particles has been hypothesized to affect the attenuation of POC flux via reduction of residence time within the water column. Here, we conducted sediment trap experiments in slope and subtropical gyre areas along the Kuroshio in the subtropical North Pacific. The ratio of POC flux at a depth 100 m below the base of the euphotic zone to that at the base of the euphotic zone (T100) varied from 0.307 to 0.646 and from 0.090 to 0.958 in the slope and subtropical gyre areas, respectively, and was positively correlated with variations in the volume-weighted mean particle diameter (Spearman rank order correlation coefficient: 0.700, p< 0.05, n = 9). However, the variation in T100 was not correlated with ambient water temperature (p > 0.05). The results support the hypothesis that attenuation of POC flux is influenced by the size of sinking particles in oligotrophic oceanic areas.